Impact of Clean and Healthy Living Education on Parental Knowledge and Independence in Supporting Child Growth at Sarfina Johor Clinic, Medan - Yesica Geovany Sianipar; Ika Damayanti Sipayung; Sonia Novita Sari; Yarman Gulo; Yeni Aprilia; Viona Manik; Sarfina Sembiring (Jurnal Kesehatan dan Kedokteran, 2026)
The first 1,000 days of life are a critical window for long-term health, yet many urban parents still prioritize curative care over preventive practices that support optimal child growth and development. Objective: This study aims to evaluate the impact of Clean and Healthy Living Behavior (CHLB) education on parental knowledge and independence in maintaining child growth and development at Sarfina Johor Clinic, Medan. Methodology: A quasi-experimental one-group pre-test and post-test design was applied. A total of 50 parents were recruited using purposive sampling. Data were collected using validated questionnaires and analyzed with the Paired Sample T-test. Findings: CHLB knowledge increased significantly from a mean of 61.44 to 87.82 (mean difference = 26.38; p = 0.000). Parental independence also improved from 56.52 to 83.24 (mean difference = 26.72; p = 0.000). Implications: Structured clinic-based education can strengthen parental self-efficacy and shift family practices toward preventive care, positioning parents as proactive managers of child health at home. This approach can be adopted by primary clinics as an operational strategy to support stunting prevention programs. Originality: This study offers a clinical-based intervention model that connects routine medical consultation with domestic health maintenance, providing a practical framework for strengthening preventive parenting practices.